Investigate an Implementation Study of TI-6AL-4V Lattice-based Scaffold Design Using Finite Element Analysis - Amit Bhumarker; Abhishek Singh (International Journal of Biochemistry and Biomolecule Research, 2023)
Implementation studies are advised to determine the effectiveness and performance of bone scaffolding in morphology, which has been demonstrated scientifically. The rehabilitation of bone defects, which is still a complex problem in orthopedic surgery, was the subject of an implementation study we provided. Biomaterial scaffolding porosity and pore size are essential in both in vivo and in vitro bone development. However, it has been linked to various drawbacks, including poor effective damping, low amounts of deformation, poor capability for absorbing energy, and mismatched bone strength and Young’s modulus (E). Therefore, metallic materials like titanium and its alloy have been studied to treat bone deformities. The research studied the mechanical characteristics of four distinct unit-cell-based architectural scaffolds. Biomaterial scaffolds with predetermined pore size and porosity were created using IntraLattice and Blender 3D software. To determine the Johnson-Cook model’s effectiveness in predicting the mechanical behavior of scaffold structures, quasi-static finite element (FE) analysis simulations using commercial CAE software were conducted. Similar to human cortical bone, the mechanical characteristics of yield strength (YS) and ultimate Young’s modulus (E) were examined. Between 2.59 and 7.65 GPa was determined to be the elastic modulus based on finite element studies.
Keywords: Finite element analysis; Porosity; pore size; scaffold; unit cell